Pengembangan Aplikasi Manajemen Notula Rapat Menggunakan Google Speech API Berbasis Android - Roliand Prasetya; Fajar Pradana; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In an organization, the number of mindsets of each member causes a difference of opinion. In order to unite the opinion together, it is necessary to conduct deliberation. one of the form of deliberation is by meeting. Faculty of Computer Science Universitas Brawijaya (FILKOM UB) is an organization that runs in education. FILKOM UB has a complex problem causing the meeting to be done repeatedly. One of solution is with the secretary which makes the notes of the meeting. However, the creation of meeting notes is still done manually so there is a possibility that meeting information can be lost. The Google Speech API is a speech recognition and can be used to record voice and convert to text to help creating meeting notes. Automatic Text Summarization with Term Frequency-Inversed Document Frequency method is automatic text summary which can be used to make conclusions from meeting notes that have been made by calculating the value or weight of a word in the document. Systems that include all the features that fit the requirements are implemented in the form of database structures, implementation of classes with Java language and interface implementation using XML language. This meeting notes management system has been successfully tested using white box testing method on unit testing and black box testing for validation testing. From these tests proves that the meeting notary management system can be used to assist the secretary in making meeting notes..